The hierarchical effects of perceived quality on perceived value, satisfaction, and loyalty - Assaker, Guy (2013)
Drawing on the literature on service quality, value, satisfaction, and loyalty, the present study assumes a hierarchical, multidimensional scheme for perceived quality focussing on four process dimensions of service quality. The aim of this study is to test a comprehensive model of perceived quality on loyalty in the context of public aquatic centres in Australia. Using partial least squares structural equation modelling (PLS-SEM) on a sample of 961 repeat customers of three outdoor public aquatic centres, results from this study reveal that four first-order process quality dimensions—facility presentation, core services, secondary services and staff—are significant in determining their higher-order perceived quality construct, with facility presentation and staff having the strongest influence. Moreover, the results of the present study indicate that overall satisfaction fully mediates the impact of perceived quality and perceived value on loyalty (behavioural intentions), with perceived quality having the strongest influence on overall satisfaction and loyalty. The present study provides an enhanced conceptualisation of the perceived quality construct in the context of public aquatic centres and contributes to the debate on the relationships among service quality, satisfaction, value, and loyalty in the sport and leisure context. In addition to strengthening theoretical understandings, the present study offers a service quality model that allows aquatic centre managers to identify specific attributes of the service that can be managed to influence loyalty more favourably.